Existentialist Critiques of Cartesianism - Dilman, Ilham. author. aut Link
XV, 179 p.
Keywords: A discussion of existentialist critiques of Cartesian epistemology, the scepticism to which it leads, its objectivist conception of the self, Cartesian dualism and solipsism and the deterministic conception of human life. By the author of "Morality and the Inner Life: A Study of Plato's 'Gorgias'".